2022
DOI: 10.1002/jat.4338
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of inhalation toxicity of cigarette smoke and aerosols from flavor mixtures: 5‐week study in A/J mice

Abstract: Most flavors used in e‐liquids are generally recognized as safe for oral consumption, but their potential effects when inhaled are not well characterized. In vivo inhalation studies of flavor ingredients in e‐liquids are scarce. A structure‐based grouping approach was used to select 38 flavor group representatives (FGR) on the basis of known and in silico‐predicted toxicological data. These FGRs were combined to create prototype e‐liquid formulations and tested against cigarette smoke (CS) in a 5‐week inhalati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 105 publications
(198 reference statements)
0
9
0
Order By: Relevance
“…Propylene glycol and glycerol are widely used in food, pharmaceuticals, cosmetics, and tobacco products. Additionally, it was demonstrated that the whole-body exposure of aerosol from the base formulation containing these two humectants to A/J mice produced no significant mortality or in-life clinical findings in 5-week study [33] . Therefore, these liquid constituents were yielded higher in DT3.0a aerosol than in 1R6F CS, suggesting less toxic property of DT3.0a aerosol compared with 1R6F CS.…”
Section: Resultsmentioning
confidence: 99%
“…Propylene glycol and glycerol are widely used in food, pharmaceuticals, cosmetics, and tobacco products. Additionally, it was demonstrated that the whole-body exposure of aerosol from the base formulation containing these two humectants to A/J mice produced no significant mortality or in-life clinical findings in 5-week study [33] . Therefore, these liquid constituents were yielded higher in DT3.0a aerosol than in 1R6F CS, suggesting less toxic property of DT3.0a aerosol compared with 1R6F CS.…”
Section: Resultsmentioning
confidence: 99%
“…After the removal of duplicates, 822 unique abstracts were screened, resulting in the inclusion of 53 studies (Figure 1, Table 1). 12‐64 Out of the 53 included articles, 34 (64%) analyzed the effects of e‐cigarette use on human subjects or cell lines, 16 (30%) utilized an animal model to investigate the in vivo effects of e‐cigarette aerosol exposure, and 3 (6%) studied both human and animal models. Human studies included: (1) in vitro assessments of e‐cigarette aerosol, condensate, or e‐liquid exposure on primary cultured cells or immortalized cell lines derived from upper airway tissue, or (2) clinical studies using samples obtained from current or former e‐cigarette users.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that smoking causes weight loss and deficient lung function 19,20 . According to Wong et al, 21 CS for 1 h daily for 5 weeks in female A/J mice induced weight loss and increased lung weight. Similarly, the instillation of WCSC in this study reduced the body weight of rats compared to the control (Figure 2A,B).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that smoking causes weight loss and deficient lung function. 19,20 According to Wong et al, 21 Inflammation plays a key role in most interstitial lung diseases, and various immune cells such as macrophages, neutrophils, and lymphocytes are actively involved in the inflammatory response. 22,23 Exposure to CS is known to increase the number of immune cells in the BALF, 24,25 which increases the risk of tissue damage by releasing toxic mediators such as proteolytic enzymes and reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%